Peningkatan Kapasitas Produksi Terasi Rebon di Desa Ketapang, Kotamadya Probolinggo - Muhamad Firdaus; Candra Adi Intyas; Yahya Yahya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Kademangan is a shrimp paste production center in the Probolinggo municipality. The shrimp paste made from this fish processing center is of lower quality than similar products on the market. The varying size of the raw materials is a significant problem in shrimp paste production in this business hub. This activity aimed to improve the quality of the shrimp paste product by introducing and enhancing the partners' skills in using grinders and shrimp powder for rebon shrimp in making rebon shrimp paste. The method of this service activity consists of training, monitoring, and evaluation of the activities. This activity showed that the partners had received training on the production of shrimp paste and its quality and the use of grinding machines and machines for boiling shrimp meal. During the partner monitoring period, it became apparent that the partners had switched the technology from manual production of shrimp paste to machine production. The evaluation results show that the partners are familiar with grinding and grinding machines in making Rebon shrimp paste. The resulting products are of higher quality than those made before the partners used the shrimp grinding shrimp flour machines. The conclusion is that the use of grinding and flour machines for rebon shrimp by partners has increased the production capacity by three times and increased the quality of the rebon shrimp paste.